HDR brachytherapy in palliative treatment of advanced esophageal cancer. Influence of previous cancer on treatment results - Skowronek, Janusz; Piotrowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2003)
Purpose: To analyze treatment results of palliative HDR brachytherapy in patients with advanced esophageal cancer treated previously for another cancer. The results were compared with those obtained in a group of patients treated for the first cancer. Material and methods: In the period from May 1999 to May 2001 in Great Poland Cancer Center there were treated 22 patients with inoperable esophageal carcinoma which were in the past treated for another cancer. All patients became disqualified from surgical treatment and radical radiotherapy due to the advance of the disease. High dose rate brachytherapy of 22.5 Gy counted in distances 1 cm from tube axis was used. A control group consisted of 91 patients treated with brachytherapy for the first cancer in the same period. Patients were subject to clinical and radiological observation rating local remission and comparing survival time with chosen clinical factors. Results: Median survival time in the first group of patients was 7.1 months, in the control group of patients – 8.2 months. No differences between these two groups were measured (log-rank test, p=0.37). Longer median survival time was observed when tumour length was below 10 cm, then when it was over 10 cm (log-rank test, p=0.001). Significant correlation was observed between the survival rate and age (log-rank test, p=0.04). Significant correlations were not found between survival and Karnofsky performance status (log-rank test, p=0.06), sex (log-rank test, p=0.12) and length of interval between tumours (log-rank test, p=0.07). Conclusions: 1. Past cancer did not have an influence on the survival of patients with advanced esophageal cancer. 2. HDR brachytherapy of advanced esophageal cancer allowed for improvement of dysphagia in most patients. 3. Length of tumour infiltration and age of patients had an influence on survival.